Rock fracture mode and acoustic emission characteristics under true triaxial single-sided unloading path - Ma, Longpei; Liu, Chongyan; Zhao, Guangming (Frontiers in Materials, 2025)
In underground engineering, the excavation and unloading processes of rocks are extremely complex. In-depth understanding of the fracture patterns of rocks and the characteristics of acoustic emission (AE) during this process is crucial for ensuring the safe and stable operation of underground engineering. In this study, a combination of the true triaxial disturbance unloading rock testing system and the acoustic emission system was adopted to conduct true triaxial single-sided unloading tests on several common rock types, including coal, siltstone, fine sandstone, and granite. At the same time, in order to analyze the experimental data more thoroughly, the Gaussian mixture model (GMM) clustering algorithm was introduced to perform clustering analysis on the characteristic parameters of acoustic emission, so as to explore the damage and fracture patterns of the unloading rocks. The findings indicate that as the peak strength of the rock decreases, the fractal dimension of the ultimately broken fragments becomes larger, and the cracks within the failure zone develop more comprehensively. The higher the peak strength of the rock after single-sided unloading is, the greater its axial average elastic modulus will be. The acoustic emission ringing count and the b-value curve indicate that compared with siltstone and fine sandstone, granite and coal are more prone to rock burst after unloading. In the RA-AF signals of coal and granite based on the GMM, the proportion of shear signals is as high as 66.05% and 69.21% respectively, which makes it easy to form shear cracks. While the proportions of tensile cracks in siltstone and fine sandstone are 41.43% and 56.41% respectively. Under the action of axial stress, they are prone to longitudinal splitting and form tensile cracks approximately parallel to the direction of the maximum principal stress. The research findings of this study are of great guiding significance for a deep understanding of the characteristics of different rocks during the excavation and unloading processes in underground engineering.